IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR - Fiqra Amaliah ZR; Suardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the implementation of learning flexibility, differentiated instruction, and the Project for Strengthening the Pancasila Student Profile (P5) within the Merdeka Curriculum at SDN 18 Kalosi, particularly in Grade IV. The background of this study is the presence of challenges in implementing student-centered learning, including teacher readiness, student characteristics, and parental involvement. This research seeks to analyze the learning practices applied, identify the obstacles and opportunities in implementing the Merdeka Curriculum, and describe teacher and school innovations in developing teaching modules and carrying out P5 activities. A descriptive qualitative approach was employed, with data collected through interviews, classroom observations, document analysis, and focus group discussions involving the school principal, teachers, students, and parents. The findings indicate that teachers have implemented flexibility by adjusting learning time, learning spaces, and instructional flow, as well as applying differentiated instruction by providing students with choices of activities and project outputs based on their interests and abilities. The implementation of P5 was conducted in a simple yet contextual manner and was able to enhance student engagement, creativity, and character development. However, several challenges were still identified, including limited teacher understanding of project-based assessment, differences in student readiness, and varying levels of parental participation. Overall, the implementation of the Merdeka Curriculum and P5 demonstrates positive progress and offers opportunities to strengthen more meaningful and student-centered learning. Keywords: Merdeka Curriculum, Differentiated Instruction, Project for Strengthening the Pancasila Student Profile (P5).